2019
DOI: 10.3390/rs11202360
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Response to Successive Typhoons Sarika and Haima (2016) Based on Data Acquired via Multiple Satellites and Moored Array

Abstract: Tropical cyclones (TCs) are natural disasters for coastal regions. TCs with maximum wind speeds higher than 32.7 m/s in the north-western Pacific are referred to as typhoons. Typhoons Sarika and Haima successively passed our moored observation array in the northern South China Sea in 2016. Based on the satellite data, the winds (clouds and rainfall) biased to the right (left) sides of the typhoon tracks. Sarika and Haima cooled the sea surface ~4 and ~2 °C and increased the salinity ~1.2 and ~0.6 psu, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…The major anomalous oceanic characteristic during super typhoon Rammasun was SST cooling after the typhoon's passage. Assessments of the daily variabilities of SST, MLD, SLA, SSW and precipitation and the relationships between them during the period of the typhoon yielded the following results: After typhoon Rammasun had passed through the SCS in July 2014, the maximal SST cooling exhibited a clear 'right-hand-side intensification' (Stramma et al, 1986;Wada, 2005;Wu et al, 2019) while heavy precipitation showed an obvious 'left-hand-side intensification' (Chen et al, 2006;Zhang et al, 2019) with respect to the typhoon track. The SST response exhibited obvious rightward biases because of the rotation resonance of the wind vector with wind-driven inertial currents (Yue et al, 2018), and precipitation response showed significant leftward biases due to vertical wind shear (Chen et al, 2006;Lin and Oey, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The major anomalous oceanic characteristic during super typhoon Rammasun was SST cooling after the typhoon's passage. Assessments of the daily variabilities of SST, MLD, SLA, SSW and precipitation and the relationships between them during the period of the typhoon yielded the following results: After typhoon Rammasun had passed through the SCS in July 2014, the maximal SST cooling exhibited a clear 'right-hand-side intensification' (Stramma et al, 1986;Wada, 2005;Wu et al, 2019) while heavy precipitation showed an obvious 'left-hand-side intensification' (Chen et al, 2006;Zhang et al, 2019) with respect to the typhoon track. The SST response exhibited obvious rightward biases because of the rotation resonance of the wind vector with wind-driven inertial currents (Yue et al, 2018), and precipitation response showed significant leftward biases due to vertical wind shear (Chen et al, 2006;Lin and Oey, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Buoys 1 and 4 show a slight SST recovery after the passage of Typhoon Kalmaegi, while at Buoys 2 and 5, the SST continues to decrease steadily. According to the literature, SST recovers within a few days to weeks [26,80,81]. It is worth noting that there is a difference in SST at the beginning of the run, which results from the initial conditions applied to ROMS.…”
Section: Sea Surface Temperaturementioning
confidence: 92%
“…The latest studies have documented the role of ocean surface waves in air-sea interactions during TC events in different parts of the world [7,[23][24][25][26][27]. Wave generation and growth are a direct effect of the surface wind.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our previous works (e.g., [2,50,[88][89][90][91][92][93]) indicate thatoceanic thermohaline and dynamic features play an important role in upper ocean response to a single or sequential typhoons based on multiple observation data and model simulations. However, these works were mainly in the marginal sea (the South China Sea) and we may further follow the study of this paper, and study how some special topographic features such as with many islands or straits influences the structure of the oceanic response to typhoons in the future.…”
Section: Future Workmentioning
confidence: 96%